2017
DOI: 10.18632/oncotarget.16689
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide combined with transcatheter artierial chemoembolzation for primary hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: ObjectiveTranscatheter arterial chemoembolization (TACE) and thalidomide have been used for treating primary hepatocellular carcinoma(HCC). This study aims to evaluate the clinical efficacy and safety of thalidomide and TACE in primary HCC.MethodsRandomized controlled trials(RCTs) about efficacy and safety of thalidomide combined with TACE for primary HCC were identified from the Cochrane Library, Pubmed, Embase, CNKI, and Wan Fang until August, 2016. The retrieved trials were reviewed and the data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…THD, as an antiangiogenic agent, has produced substantial clinical benefits in the treatment of multiple myeloma, and its effects on a host of solid tumors have been quite variable. There seems to be a reasonable consensus that THD has demonstrable tumoristatic effects in renal cell carcinoma [49], hepatocellular carcinoma [50,51], prostate carcinoma [52], Kaposi's sarcoma [53], melanoma [54], glioma [55], and glioblastoma multiforme [56]. The main pathophysiological features of advanced cancer are insomnia, chronic emesis, nausea, cachexia, metabolic disorders, and tumor-associated pain as well as decreased sensation of wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…THD, as an antiangiogenic agent, has produced substantial clinical benefits in the treatment of multiple myeloma, and its effects on a host of solid tumors have been quite variable. There seems to be a reasonable consensus that THD has demonstrable tumoristatic effects in renal cell carcinoma [49], hepatocellular carcinoma [50,51], prostate carcinoma [52], Kaposi's sarcoma [53], melanoma [54], glioma [55], and glioblastoma multiforme [56]. The main pathophysiological features of advanced cancer are insomnia, chronic emesis, nausea, cachexia, metabolic disorders, and tumor-associated pain as well as decreased sensation of wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide, is a glutamic acid derivative, which was a classic drug with immunemodulatory properties and tumor necrosis factor alpha inhibits [50][51][52]. Subsequent studies found that thalidomide has anti-angiogenic, anti-in ammatory, anti-brotic and immune-modulatory effects, and the clinical effectiveness of thalidomide has been con rmed in the treatment of certain disease such as refractory Crohn's disease, lung metastasis, multiple myeloma, hepatocellular carcinoma, and breast carcinoma [53][54][55][56][57][58][59][60]. Our results based on the CMAP database may provide several potential smallmolecule drugs as to future therapy for NPC; nevertheless, studies in vivo and in vitro experiments are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Furthermore, Cao's findings suggest that thalidomide combined with TACE shows better clinical efficacy and tolerable adverse events in patients with primary HCC when compared with TACE alone. [30] Li et al . presented that it is safe and effective to use TACE combined with microwave ablation in the treatment of advanced HCC, and the effect of combined treatment is better than that of TACE alone.…”
Section: Discussionmentioning
confidence: 99%